Investigation into discrete molecular catalysts for biomass conversion into 5-hydroxymethylfurfural - Dunn, Eric F., author; Chen, Eugene Y.-X., advisor; Finke, Richard G., committee member; Bjostad, Louis B., committee member (Colorado State University. Libraries, 2013)
As part of ongoing research into the conversion of biomass into the platform chemical 5-hydroxymethylfurfural (HMF), two primary investigations have been performed. The first is an exploration of discrete lanthanide complexes as possible catalysts for the conversion of glucose to HMF. Catalysts of the type Ln(HMDS)3, Ln(MeTMS)3, and Ln(OTf)3 have been examined in ionic liquid (IL) for their performance in the glucose-to-HMF conversion. In this study Sc(OTf)3 has been identified as a good catalyst for both glucose (up to 38% HMF yield) and cellulose (up to 19% HMF yield) conversions. The second investigation was concerned with the effect of N-heterocyclic carbenes (NHCs) on the biomass conversion system that containing IL solvents. Since NHC's can be readily formed from deprotonation of ILs, there exists in the literature the hypothesis that an NHC-CrClx complex is the true catalyst in these conversion systems. Three sets of experiments are reported herein to test this hypothesis: controls with all additives used by previous investigations purporting an NHC effect, tests of in situ generated and discrete preformed NHC-Cr complexes suggested by the hypothesis, and quantitative NHC titration (poisoning) experiments. The combined evidence shows conclusively that the NHC ligand actually serves as a poison to the chromium catalyst system and that a superstoichiometric amount (2 or 3 equiv) of NHC ligand can completely shut down the catalysis.
Keywords: 5-hydroxymethylfurfural; biomass; chromium; glucose; Ionic liquids; N-heterocyclic carbene